The future of the Asian auto industry: regional integration, alternative designs, and Chinese leadership. (12th May 2004) - Veloso, Francisco; Fuchs, Erica
This paper provides a critical analysis of the key drivers behind the future of the automotive industry in Asia. It argues that three changes will condition the evolution of the Asian auto sector. First, the Asian region will rapidly progress towards an integrated market and, as a whole, will play a central role in the global automotive industry. Second, alternative vehicle designs specific to the emerging Asian markets can be expected to emerge and form a second tier market. Political and economic advantages exist for the bodies of these vehicles being of fiber-composite resin materials instead of the steel of traditional vehicles. Finally, China will increasingly play a leadership role in the region, driving the regional economic integration process and establishing itself as critical base and destination for automakers and suppliers. The paper also addresses the evolving regional division of labor in Asia and how differences across countries, automakers, and suppliers may play a role in the emerging context.